Capacitance spectroscopy of InAs self-assembled quantum dots - Martin, P.M.; Belyaev, A.E.; Eaves, L.; Main, P.C.; Sheard, F.W.; Ihn, T.; Henini, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
Capacitance spectroscopy is used to study electronic properties of self-assembled InAs quantum dots. The capacitance-voltage, C(V), measurements in combination with the magneto-capacitance, C(B), results make it possible to investigate the electrostatic profile of a series of single-barrier n-i-n GaAs/AlAs/GaAs heterostructures incorporating a layer of self-assembled InAs quantum dots in the AlAs barrier. We find that the negative charge associated with electron filling of the dots is closely compensated by a positive charge in the AlAs barrier, which we ascribe to ionised defects or impurities, possibly in association with the quantum dots. It is shown the compensation degree considerably depends on the growth conditions. Ємнiсна спектроскопiя використується для дослiдження електронних властивостей само-органiзованих InAs квантових точок. Вимiрювання вольт-фарадних характеристик, C(V), одночасно з даними по магнето-емностi, C(B), дозволяють дослiджувати електростатичний профiль однобар.єрних p-i-n GaAs/AlAs/GaAs гетероструктур, якi мiстять в AlAs бар.єрі шар само-органiзованих InAs квантових точок. Ми визначили, що негативний заряд, пов.язаний з заповненням квантових точок електронами, майже повнiстю компенсується позитивним зарядом в AlAs бар.єрi, що, на нашу думку, пов.язано з iонiзованими дефектами чи домiшками, якi обумовлені квантовими точками. Показано, що мiра компенсацiї суттєво залежить вiд ростових умов. Емкостная спектроскопия используется для исследования электронных свойств само-организованных InAs квантовых точек. Измерение вольт-фарадных характеристик, C(V), совместно с данными по магнето-емкости, C(B), позволяют исследовать электростатический профиль однобарьерных p-i-n GaAs/AlAs/GaAs гетероструктур, содержащих в AlAs барьере слой само-организованных InAs квантовых точек. Мы установили, что отрицательный заряд, связанный с заполнением квантовых точек электронами, почти полностью компенсируется положительным зарядом в AlAs барьере, который, по нашему мнению, связан с ионизованными дефектами или примесями, обусловленными квантовыми точками. Показано, что степень компенсации существенно зависит от ростовых условий.